The Effect of EDM Die-Sinking Parameters on Material Characteristic for Aluminium Composite Using Tungsten Copper Electrode - Md Ali, Mohd Amran; Laily, Suraya; Nor, Halida Ilyani Kamarudin; Hussein, Nur Izan Syahriah; Muhamad, Mohd Razali; Manshoor, Bukhari; Lajis, Mohd Amri; Raja Izamshah , Raja Abdullah; Abu Bakar, Mohd Hadzley; Taufik, Roni Sahroni (2014)
The machining ability of electrical discharge machining (EDM) die-sinking on aluminium LM6 (Al-Sil2) as a new material is investigated.The objective of this paper is to determine the relationship between the machining parameters which are pulse-on time, pulse-off time and peak current on the material characteristics such as material removal rate (MRR), electrode wear rate (EWR) and surface roughness (Ra). Tungsten copper tool of diameter 10mm was chosen as an electrode. Design of experiment using Taguchi method was used to develop experimental matrix and optimize the MRR, EWR and Ra. The analysis was done using the Minitab software. It is found that the current and pulse on time are significantly affected the MRR, EWR and Ra while pulse off time and voltage are less significant factor that affected the responses. From the Taguchi method, the best setting of optimum value was obtained. Thus, it shows that Taguchi method is the best quality tools that can be applied for production.